A highly efficient Au-MoS2 nanocatalyst for tunable piezocatalytic and photocatalytic water disinfection. (March 2019) - Chou, Ting-Mao; Chan, Shuen-Wen; Lin, Yu-Jiung; Yang, Po-Kang; Liu, Chia-Chen; Lin, Yu-Jhen; Wu, Jyh-Ming; Lee, Jyun-Ting; Lin, Zong-Hong
Abstract: Clean water is essential in our daily life. However, nearly one billion people are forced to drink water contaminated with bacteria, leading to diarrhea, dehydration, and even death. Previously, various photocatalysts have been applied to replace high-cost and highly toxic methods for sewage treatment. Nevertheless, the requirement of external light sources limits their application. Herein, we develop a new type of nanocatalyst based on single- and few-layered molybdenum disulfide (MoS2 ) nanosheets (NSs) that can catalyze the generation of reactive oxygen species (ROS) to inactivate bacteria either through a piezoelectric effect (mechanical vibration) or photocatalytic effect (light irradiation). After 60 min of mechanical vibration or visible-light irradiation, the MoS2 NSs can reduce Escherichia coli (E. Coli) by 99.999%. In addition, the ROS generation efficiency and bacterial disinfection performance of the catalyst can be enhanced by depositing Au nanoparticles (NPs) on MoS2 NSs. The period of mechanical vibration or visible-light irradiation that achieves the same 99.999% reduction in E. coli is shortened to 45 min. Moreover, a hybridization of the piezoelectric and photocatalytic effects results in a performance superior to that obtained with the individual effects. A 99.999% reduction in E. coli is also accomplished within 15 min through a combination of mechanical vibration and near-infrared (NIR)-light irradiation. This MoS2 nanocatalyst is a promising candidate for nextgeneration water purification systems because of its ability to be triggered by diverse environmental stimuli. Graphical abstract: A highly efficient Au-MoS2 nanocatalyst that can be triggered by ambient mechanical vibration and light irradiation has been developed. The tunable piezocatalytic and photocatalytic effects enable the Au-MoS2 nanocatalyst to generate reactive oxygen species and result in superior disinfection performance. fx1 Highlights: Au-MoS2 nanosheets (NSs) as a highly efficient nanocatalyst for water disinfection has been demonstrated in this paper. The Au-MoS2 NSs shows the flexibility to generate reactive oxygen species by mechanical vibration or light irradiation. The amount of generated reactive oxygen species is controllable and used to achieve a superior disinfection performance. The hybridization of piezocatalytic and photocatalytic effects results in a 99.999% bacterial reduction within 15 minutes.